The Influence of Underwriter Reputation and Company Size on Underpricing Moderated with Financial Performance in Companies Conducting IPO’s on The IDX During The Covid-19 Pandemic - Aprianto, Junaidi; Mikial, Msy; Noviantoro, Djatmiko; Susanti, Eva (Journal of Management, 2024)
This research aims to determine and prove the influence of underwriter reputation and company size on underpricing with financial performance as a moderating variable in companies that conducted initial public offerings (IPOs) on the IDX during the 2020 COVID-19 pandemic, both directly and indirectly. The population in this research are public companies listed on the Indonesia Stock Exchange in 2020-2021 and have conducted an IPO. The number of samples in this study was 24 companies with a sampling technique using the purposive sampling method. The analytical method used is moderated regression analysis (MRA). The research results show that partially Underwriter Reputation and Company Size influence Financial Performance. Underwriter reputation and company size influence underpricing. Financial Performance influences Underpricing. Financial Performance can strengthen the influence of Underwriter Reputation on Underpricing. Financial Performance can strengthen the influence of Company Size on Underpricing. The findings of this research can add insight and be a positive signal for potential investors in assessing the quality of the company and reducing the level of uncertainty. This research can also be used as a consideration for companies in determining share prices. This research provides new insights regarding underpricing moderating the influence of Underwriter Reputation and Company Size on financial performance.